Breeding programme for developing new sweet cherry cultivars in the Fruit Growing Institute, Plovdiv, Bulgaria - S. Malchev (Agricultural Science and Technology, 2016)
Abstract. Sweet cherry is a major structural species in Bulgaria. According to the Ministry of Agriculture and Food, in 2010 it occupied 21% of the fruit tree areas, which defined it as a leading fruit crop. It represents 16% of the total fruit production in the country, as is the relative share of peach, being surpassed only by apple and plum production. The increased interest in establishing new cherry plantations necessitates the provision of new market-oriented cultivars with a better sensory profile of the fruits, resistant to biotic and abiotic stress factors, suitable for creating modern intensive cherry plantations. The Bulgarian sweet cherry cultivars are chronologically discussed and a thorough description of the development of the sweet cherry breeding programme, launched at the Fruit Growing Institute in Plovdiv in 1987, is presented. Current objectives comply with the world's major breeding trends and the changing market requirements. The paper reflects the main objectives of the programme and the finalized products obtained in the last twenty years of the past century and first decade of the new millennium, i.e. the new cultivars 'Kossara', 'Rosita', 'Rozalina' and 'Thrakiiska hrushtyalka' and some promising hybrids.